2020
DOI: 10.1590/1806-9282.66.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory predictors of survival in ovarian cancer

Abstract: SUMMARY OBJECTIVE To relate disease-free survival and overall survival with type I and type II ovarian cancer and preoperative laboratory parameters biomarkers. METHODS A retrospective study was carried out based on the collection of data from medical records of patients with ovarian tumors. Kaplan-Mayer curves were drawn based on the statistical analysis of the data and were compared using the Log-rank test. RESULTS Disease-free survival in type I ovarian cancer was significantly higher than in type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…However, as ovarian torsion is an acute inflammatory condition, markers such as WBC, Creactive protein (CRP), and D-dimer may increase in response to inflammation (15). An experimental study found that D-dimer levels were elevated in cases of ovarian torsion (16). CRP, an acute-phase reactant that rises in inflammatory events, has been emphasized to have diagnostic value in acute abdominal pain by Chi and colleagues (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, as ovarian torsion is an acute inflammatory condition, markers such as WBC, Creactive protein (CRP), and D-dimer may increase in response to inflammation (15). An experimental study found that D-dimer levels were elevated in cases of ovarian torsion (16). CRP, an acute-phase reactant that rises in inflammatory events, has been emphasized to have diagnostic value in acute abdominal pain by Chi and colleagues (17).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of GLUT1 is associated with shorter survival times in ovarian cancer patients and predicts a shorter time for recurrence (DFI) in patients who achieve remission. [16][17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%